2003
DOI: 10.1161/01.cir.0000049742.68848.99
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Plasma Levels of Monocyte Chemoattractant Protein-1 and Long-Term Clinical Outcomes in Patients With Acute Coronary Syndromes

Abstract: Background-Monocyte chemoattractant protein-1 (MCP-1) is a chemokine responsible for the recruitment of monocytes to sites of inflammation. MCP-1 appears to play a critical role at multiple stages in atherosclerosis, including the initiation of the fatty streak, promotion of plaque instability, and remodeling after myocardial infarction. After adjustment for differences in baseline characteristics, ECG changes, troponin I, and C-reactive protein, an MCP-1 level Ͼ75th percentile (corresponding to the 90th perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
244
6
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 409 publications
(281 citation statements)
references
References 47 publications
17
244
6
7
Order By: Relevance
“…Our findings of decreased plasma MCP-1 levels in carriers of the G allele are in agreement with data in patients with lupus nephritis [25]. In the present study, plasma MCP-1 levels were significantly and positively correlated with markers of the metabolic syndrome, such as insulin resistance, Type 2 diabetes, hypertension, obesity, WHR, high triglycerides and low HDL [36,37]. Conversely, another study showed that insulin infusion results in decreased plasma MCP-1 levels in obese subjects [38].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings of decreased plasma MCP-1 levels in carriers of the G allele are in agreement with data in patients with lupus nephritis [25]. In the present study, plasma MCP-1 levels were significantly and positively correlated with markers of the metabolic syndrome, such as insulin resistance, Type 2 diabetes, hypertension, obesity, WHR, high triglycerides and low HDL [36,37]. Conversely, another study showed that insulin infusion results in decreased plasma MCP-1 levels in obese subjects [38].…”
Section: Discussionsupporting
confidence: 92%
“…We report an association of SAA1 with all‐cause and CVD mortality. MCP1 is a chemokine that regulates monocyte trafficking and previously has been associated with myocardial infarction in FHS and adverse outcomes in patients with acute coronary syndrome 39, 40. sGP130 is a natural inhibitor of IL6 responses and has been associated with adverse outcomes among ischemic HF patients 41.…”
Section: Discussionmentioning
confidence: 99%
“…4 In human studies, serum levels of MCP-1 have been associated with older age, female sex, hypertension, diabetes, history of coronary disease, renal insufficiency, measures of adiposity and other inflammatory mediators including C-reactive protein (CRP), interleukin-6, interleukin-18, interleukin-8 and IP-10. [5][6][7] However, the relationship between levels of MCP-1 and risk of atherosclerotic diseases is inconsistent. Researchers using the Framingham Heart Study cohort reported that allele À2578G in the MCP-1 gene was significantly associated with increased serum levels of MCP-1 and a higher prevalence of myocardial infarction (MI).…”
Section: Introductionmentioning
confidence: 99%